Тhe main stakeholders and the policy of development of small and medium-sized businesses in the republic of kazakhstan - Seytkalieva, Zh. A.; Dosalieva, A. M.; Ayesheva, G. A. (Жәңгір хан атындағы БҚАТУ, 2023)
In this article, we propose a business model for the production of fish and fish products based on the use of an innovative combined resource-saving technology. В данной статье нами предлагается бизнес-модель производства рыбы и рыбной продукции на основе использования инновационной комбинированной ресурсосберегающей технологии.
«ҒЫЛЫМҒА ЖОЛ – 2023» білім алушыларға арналған халықаралық ғылыми-тәжірибелік конференциясының МАТЕРИАЛДАР ЖИНАҒЫ
СБОРНИК МАТЕРИАЛОВ Международной научно-практической конференции обучающихся «ПУТЬ В НАУКУ – 2023»
47 S52 Seytkalieva, Zh. A. Тhe main stakeholders and the policy of development of small and medium-sized businesses in the republic of kazakhstan / Zh. A. Seytkalieva, A. M. Dosalieva, G. A. Ayesheva. - Текст : непосредственный // Ғылымға жол-2023: білім алушыларға арналған халықаралық ғылыми-тәжірибелік конф. мат. жинағы (12 сәуір 2023 ж.). = Путь в науку-2023: сб. мат. междунар. науч.-практ. конф. обучающихся (12 апреля 2023 г.). = THE PATH TO SCIENCE – 2023: collected papers of the International Scientific-Practical Conference of students (12th of April, 2023). - Орал: Жәңгір хан атындағы БҚАТУ. - 2023. - Т. ІІ. - Б. 421-425 (Орал)
Keywords: отечественное издание; ЗКАТУ; конференции; fisheries; business model; рыбное хозяйство; рыбоводство; рынок